The effect of side-chain substitution and hot processing on diketopyrrolopyrrole-based polymers for organic solar cells - Heintges, Gaël H. L. (Royal Society of Chemistry, 2017)

(untitled) (J Mater Chem A Mater Energy Sustain)
The effects of cold and hot processing on the performance of polymer–fullerene solar cells are investigated for diketopyrrolopyrrole (DPP) based polymers that were specifically designed and synthesized to exhibit a strong temperature-dependent aggregation in solution. The polymers, consisting of alternating DPP and oligothiophene units, are substituted with linear and second position branched alkyl side chains. For the polymer–fullerene blends that can be processed at room temperature, hot processing does not enhance the power conversion efficiencies compared to cold processing because the increased solubility at elevated temperatures results in the formation of wider polymer fibres that reduce charge generation. Instead, hot processing seems to be advantageous when cold processing is not possible due to a limited solubility at room temperature. The resulting morphologies are consistent with a nucleation-growth mechanism for polymer fibres during drying of the films.